Interventions to Improve Quality of Life Among Patients with Breast Cancer: A Scoping Review - Aep Maulid Mulyana; Hesti Platini; Risma Dwi Nur Pratiwi; Sidik Maulana (Jurnal EduHealth, 2023)
Breast cancer is the most common cancer that affects women and can impact the quality of life (QoL) of patients. Objective: The aim of this study is to identify interventions to improve the QoL of breast cancer patients. Method: This study uses a systematic scoping review approach on Pubmed, CINAHL, Cochrane Library, and ScienceDirect with a publication range of articles from 2018-2022, full-text articles, and randomized controlled trials. The quality assessment of the study uses critical appraisal checklist tools for randomized controlled trial research from the Joanna Briggs Institute (JBI). Results: Overall, 11 studies found interventions that are effective in improving the QoL of breast cancer patients, including nutritional counseling, Qigong, Yoga, music therapy, lymphedema self-management education, adapted physical activity and diet "APAD," patient-centered self-management support programs, Calorie Restriction and Synbiotics (CRS), and patient navigation. Recommendation: Our study highlights the potential of self-management approaches to improve the QoL of breast cancer patients. These findings can be a recommendation for nurses and other healthcare professionals in determining interventions to improve the QoL of breast cancer patients.